Գրիգոր Օշականցու տաղերի լեզուն եւ ոճը - Յովհաննիսեան, Աստղիկ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Архиепископ Григор Ошаканци — восточноармянский поэт XVIII века. Его произведения и рукописи были собраны Ованнесом Карнеци. Основная тема Григора Ошаканци — восхваление и прославление родной природы с реалистичным, объективным, простым и доступным описанием. Основная лексика произведений Ошаканци — древнеармянская. Помимо исконно армянской лексики, переданной через грабар, Ошаканци использует ряд реалий, характерных для грамматики этого языка. Ошканци также использует ряд заимствованных слов из сирийскго( арамейского), греческого, иврита, пехлевийского и персидского языков. Он один из тех авторов Средневековья, который представляется нам ценными по меркам своего времени стихами, отличающимися тонкостью, живым, красноречивым описанием художественных образов, богатым и полным словарным запасом. Грабарские (классический армянский язык) и ашхарабарские (новый армянский язык) грамматико-лексические и стилистические реалии, обнаруженные в творчестве Григора Ошаканци, подготовили почву для формирования двух ветвей ашхарабарского армянского, особенно для языковых компонентов западноармянского языка. Archbishop Grigor Oshakantsi was an 18th century Eastern Armenian poet. His works and manuscripts were collected by Hovhannes Karnetsi. The main theme of Grigor Oshakantsi is the praise and glorification of native nature in objective, simple and comprehensible description. The basic vocabulary of Oshakantsi’s works belongs to the Classical Armenian language. In addition to the native Armenian vocabulary conveyed through the Classical Armenian, Oshakantsi uses a number of facts characteristic of the grammar of the Classical Armenian. Oshakantsi also uses a number of loanwords from Assyrian, Greek, Hebrew, Pahlavi and Persian. He is one of those medieval authors who present valuable poems by the standards of their time, characterized by subtlety, vivid, eloquent description of artistic images and rich vocabulary. The linguistic and stylistic realities of the Classical Armenian and Modern Armenian languages found in the works of Grigor Oshakantsi prepared subsoil for the formation of two branches of the Modern Armenian language, especially for the substantiation of the linguistic components of the Western Armenian.
Keywords: Հաղորդումներ; Բանասիրութիւն